MICROFINANCE AND FACTORS CONTRIBUTING FOR ECONOMIC EMPOWERMENT OF SHG WOMEN: A CASE - M Mr. Vijaya Kumar, R S & Dr. S Harish Babu (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Empowerment refers to increasing the decision taking ability of people in general and women in particular. Economic empowerment of women is basically decision taking authority of women on economic issues and having ownership over economic resources. One of the overriding approaches to rural women economic empowerment is configuration of women through Micro finance predominantly in rural areas. The present paper an attempt has made to analyze the factors contributing for economic empowerment of women. The principal component analysis has used for the purpose using primary data collected in Hassan district. It has been found from the study that the economic empowerment is possible in many ways and economic activities. Out of 20 ways of achieving the economic empowerment, the feasibility has found only in six ways. Hence, the absolute economic empowerment of SHG women has not achieved in Hassan district. However, the relative economic empowerment has been achieved with the help of bank linkage SHG programme. It has been proved by the study that lack of income earning employment opportunities are the hurdles in achieving the efficient economic empowerment of women. Therefore, the promoting agencies of SHGs have to financially support the income earning activities of the SHG women members.